The European Water Framework Directive at the age of 10: A critical review of the achievements with recommendations for the future - Hering, Daniel; Borja, Angel; Carstensen, Jacob; Carvalho, Laurence; Elliott, Mike; Feld, Christian K.; Heiskanen, Anna-Stiina; Johnson, Richard K.; Moe, Jannicke; Pont, Didier; Solheim, Anne Lyche; de Bund, Wouter van (The Science of the total environment, 2010)
The European Water Framework Directive (WFD), which was adopted in 2000, changed water management in all member states of the European Union fundamentally, putting aquatic ecology at the base of management decisions. Here we review the successes and problems encountered with implementation of the WFD over the past 10 years and provide recommendations to further improve the implementation process. We particularly address three fields: (i) the development of assessment methods (including reference conditions, typologies and intercalibration); (ii) the implementation of assessment systems in monitoring programmes; and (iii) the consequences for river basin management plans (such as the design, monitoring and success of restoration measures). The development of assessment methods has been a transparent process and has resulted in improved and more standardised tools for assessing water bodies across Europe. The process has been more time consuming, and methods are more complex, than originally expected. Future challenges still remain, including the estimation of uncertainty of assessment results and a revision of rules in combining the results obtained with different Biological Quality Elements. A huge amount of monitoring data is now being generated for WFD purposes. Monitoring data are not centrally stored and thus poorly accessible for purposes beyond the WFD. Future challenges include enhanced data accessibility and the establishment of a Europe-wide central monitoring network of reference sites. The WFD river basin management plans base management decisions on the response of aquatic organisms to environmental stress. In contrast to the effects of degradation, the biotic response to restoration is less well-known and poorly predictable. The timescale of the WFD (obtaining good ecological status in all surface waters by 2027) is over-ambitious. Future challenges include long-term monitoring of restoration measures to understand the requirements for ecosystems to recover and prioritisation of measures according to re-colonisation potential.